Hubungan Nyeri Rheumatoid Arthritis dengan Kemandirian ADL pada Lansia - Mariya Yusefa; Wisnu Probo Wijayanto; Sutrisno Sutrisno; Didi Suswantoro4 (Jurnal Ilmu Medis Indonesia, 2023)
Purpose: The research objective was to determine the correlation between rheumatoid arthritis pain with the independent activity of daily living on the elderly at the Kalibalangan Village of South Abung District in North Lampung Regency 2022. Method: The research objective was to determine the correlation between rheumatoid arthritis pain with the independent activity of daily living on the elderly at the Kalibalangan Village of South Abung District in North Lampung Regency 2022. Results: The results showed that most of the 54.2% (39 people) were elderly with mild rheumatoid arthritis pain levels. Most of the respondents have an independent level of 56.9% (41 people). There is a correlation between rheumatoid arthritis pain with the independent activity of daily living in the elderly at the Kalibalangan Village of North Lampung Regency in 2022. The statistical test results obtained a p-value of 0.003 (<0.05) and an odd ratio/risk factor (OR) of 5.075. Contribution: By conducting this research, researchers expect that health care workers can improve the quality of services, especially for the elderly.